Draft Eighth Five Year Plan 1990-95 and Annual Plan 1991-92 Union Territory of Delhi - Planning Commission (Planning Commission, 1990)
Covering of storm, water drains and using them for recreation, transportation and commercial purposes.
Planning Department Delhi Administration
Planning Department Delhi Administration